BRAFV600E Mutation-Responsive miRNA-222-3p Promotes Metastasis of Papillary Thyroid Cancer Cells via Snail-Induced EMT - Gao, Yuan; Xiang, Dapeng; Li, Weijie; Zheng, Xi; Wang, Lin; Li, Zhiyu; Chen, Ting (Frontiers in Endocrinology, 2022)
BRAF mutation accounts for 50% of the PTC (papillary thyroid carcinoma) and is closely associated with high-risk clinicopathological characteristics. Increasing evidence implied that dysregulation of miRNA participated in carcinogenesis and progression of cancer. Clinical data showed the significant up-regulation of miR-222-3p in PTC; however, the role of miR-222-3p and possible relationship with BRAF mutation remained unclear. Here, we identified significant up-regulation of miR-222-3p in PTC tissues harboring BRAFV600E mutation compared with BRAF wild type (BRAFWT) from collected PTC clinical samples. External validation performed with The Cancer Genome Atlas (TCGA) databases was consistent with the above result. Exogenous expression of BRAFV600E oncoprotein increased the expression of miR-222-3p in B-CPAP and TPC-1 cells. The treatment of BRAFV600E and MEK inhibitor, PLX4720 and PD0325901, decreased the expression of miR-222-3p in B-CPAP but not in TPC-1. Inhibition of miR-222-3p significantly suppressed the migration of B-CPAP and induced a mesenchymal-epithelial transition (MET) phenotype via the Snail transcription factor. Immunohistochemistry (IHC) analysis demonstrated the up-regulation of Snail correlated with lymph node metastasis and BRAFV600E mutation in PTC. Besides, in situ hybridization (ISH) and IHC analysis of PTC clinical samples confirmed the correlation between the expression of miR-222-3p and Snail. These results showed miR-222-3p conduced more aggressive clinical manifestation of PTC by promoting Snail-induced EMT.